Lipidation states orchestrate CLICK-III/CaMKIγ's stepwise association with Golgi and rafts-enriched membranes and specify its functional coupling to STEF-Rac1-dependent neurite extension - Ageta-Ishihara, Natsumi; Takemoto-Kimura, Sayaka; Kondo, Yayoi; Okamura, Michiko; Bito, Haruhiko (Frontiers in Cellular Neuroscience, 2023)
Formation of axodendritic polarity and neurite growth are critical events in early circuit formation and brain development. Misregulation of these elementary processes are linked to various forms of neuropsychiatric disorders. Dysfunction of cytoskeletal remodeling may also underlie neurodegeneration in several intractable diseases such as Alzheimer's disease, while also impacting on the recovery from spinal cord injuries. In spite of a growing list of molecular players involved in the mechanisms of neuritogenesis, the compartmentalization of these signaling events to specific axodendritic segments of a neuron is not fully understood. Previously, we found that within the same kinase family, a membrane-anchored CaMKIγ promoted dendrite extension, while a cytoplasmic